Regulation and Function of Chemokines at the Maternal–Fetal Interface - Zhang, Sainan; Ding, Jinli; Zhang, Yan; Liu, Su; Yang, Jing; Yin, Tailang (Frontiers in Cell and Developmental Biology, 2022)
Successful pregnancy requires the maternal immune system to tolerate the semi-allogeneic embryo. Good trophoblast function is also essential for successful embryo implantation and subsequent placental development. Chemokines are initially described in recruiting leukocytes. There is a rich chemokines and chemokine receptors system at the maternal-fetal interface. Numerous studies have reported that they not only regulate trophoblast biological behaviors but also participate in the decidual immune response. At the same time, the chemokine system builds an important communication network between fetally-derived trophoblast cells and maternally-derived decidual cells. However, abnormal functions of chemokines or chemokine receptors are involved in a series of pregnancy complications. As growing evidence points to the roles of chemokines in pregnancy, there is a great need to summarize the available data on this topic. This review aims to describe the recent research progress on the regulation and function of the main chemokines in pregnancy at the maternal-fetal interface. In addition, we also discuss the potential relationship between chemokines and pregnancy complications.